METHODS OF INVESTIGATION OF THERMAL PROCESSES IN THE ARMATURES OF THE MOTORS SWITCH PROCESSES IN THE ARMATURES OF THE MOTORS SWITCH ACTUATORS - Parfenov, V. I.; Razghonov, O. P.; Rudenko, O. B. (Science and Transport Progress, 2007)
The article considers issues of experimental research of thermal processes in the anchors of d. c. electrical motors in electrical drives of railway switching points. It has been proposed to determine the temperature of winding anchor insulation by the value of its capacity. This method allows to increase reliability and accuracy ofd.c.electrical motors diagnostics.